Corporate Social Responsibility (CSR) sebagai Instrumen Kebijakan Publik: Analisis Dampak Program CSR Perusahaan Perkebunan di Merauke - Hombore, Esau (Indo Publishing, 2025)
This study aims to analyze how Corporate Social Responsibility (CSR) programs run by plantation companies in Merauke Regency contribute to local development and the extent to which CSR can be positioned as an instrument of regional public policy. Using a qualitative approach, data were collected through in-depth interviews, participatory observations, and documentation studies of various actors, including company representatives, local governments, and local communities. The results of the study indicate that although CSR programs have the potential to support basic social services and community economic empowerment, their implementation still faces a number of challenges, such as weak regulations, minimal community participation, and unequal distribution of benefits. In addition, most CSR programs are still top-down and not fully contextual to local values. This study emphasizes the need to integrate CSR into regional development planning through strengthening the regulatory framework, participatory monitoring mechanisms, and mainstreaming local wisdom. Thus, CSR is not only a moral obligation of companies, but can be transformed into an instrument of inclusive and sustainable regional development governance.